Integrating strength and power development in the long-term athletic development of young Rugby Union players: Methodological and practical applications - Durguerian, A.; Piscione, J.; Mathieu, B.; Lacome, M. (Strength and Conditioning Journal, 2019)
The purpose of this article is to describe the training strategy built by the french rugby union to optimize strength and power development in elite rugby union players. The training process is based on 4 stages composed of educational and technical efficiency, work capacity, maximal strength, and explosive power. The evolution of the player during these different steps should be adjusted according to individual progression and not only their chronological and biological age. Supervised training sessions with qualified and experienced strength and conditioning coaches are paramount to ensure individualized training and provide sound pedagogical approaches.